Pengaruh Food Ingredients, Sertifikasi Halal, dan Religiusitas Terhadap Minat Beli Makanan Olahan Halal - Siti Titta Partini (Bulletin of Management and Business, 2022)
This study uses a quantitative verification method with the aim of analyzing the effect of Food Ingredients, Halal Certification and Religiosity on Purchase Intention of Halal Processed Food. The sampling technique used accidental technical sampling for primary data, with 125 Muslim respondents living in various cities in Java and outside Java. Sampling using googleform and data processing with SPSS software. The results showed that simultaneously food ingredients, halal certification and religiosity had a significant and positive effect on purchase intention of halal processed foods. Partially, food ingredients and halal certification have a significant effect, while religiosity has no significant effect on purchase intention of halal processed food. The number of respondents and the limited number of independent variables can affect the accuracy of research results, so it is hoped that further similar research can add to it so that research results are better and more accurate.